2022
DOI: 10.3390/foods11101500
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Customer Reviews of Food Delivery Services Using Deep Learning and Explainable Artificial Intelligence: Systematic Review

Abstract: During the COVID-19 crisis, customers’ preference in having food delivered to their doorstep instead of waiting in a restaurant has propelled the growth of food delivery services (FDSs). With all restaurants going online and bringing FDSs onboard, such as UberEATS, Menulog or Deliveroo, customer reviews on online platforms have become an important source of information about the company’s performance. FDS organisations aim to gather complaints from customer feedback and effectively use the data to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Over the past couple of decades, there has been a good amount of research published on the application of ML techniques to perform sentiment analysis in the FDS domain [ 13 , 28 , 29 , 30 , 31 ]. Sentiment analysis of customer reviews from tweets for various FDSs, such as Swiggy, Zomato and Uber Eats, was performed to understand consumer satisfaction [ 32 ].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past couple of decades, there has been a good amount of research published on the application of ML techniques to perform sentiment analysis in the FDS domain [ 13 , 28 , 29 , 30 , 31 ]. Sentiment analysis of customer reviews from tweets for various FDSs, such as Swiggy, Zomato and Uber Eats, was performed to understand consumer satisfaction [ 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…In another significant work, Noor [ 33 ] compared the results of Lexicon, SVM, Natural Language Processing (NLP) and Text Mining from different works and found that Lexicon achieved the highest accuracy of 87.33% compared to other methods. However, it would be difficult to perform a sentiment analysis in languages other than English [ 13 ]. Additionally, domain adaptation must be taken into account while creating models because a word in one domain may have a different meaning in another.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations